Effects of modern dance programs on improving health-related physical fitness in girls - Ilić, Aleksandra; Marinkovic, Dragan; Herodek, Romina; Vlašić, Jadranka; Jovanović, Saša (Frontiers in Public Health, 2024)
IntroductionAs creative physical activity influences many aspects of child development—including physical, social, and emotional wellbeing—the effects of two experimental modern dance programs on the development of health-related physical fitness in young school-aged girls were assessed in this longitudinal study.Materials and methodsThe study sample comprised 203 girls aged 7–11 years, 102 of whom (the control group) were recruited from the elementary school “Vuk Karadžić” from Bačka Palanka, while Experimental Group 1 (n = 51) and Experimental Group 2 (n = 50) respectively consisted of girls who have been involved in a modern dance program for no longer than 1 year and at least 2 years. The participants were also divided into AGE 1 (7–9 years, n = 103) and AGE 2 (9–11 years, n = 100) groups to assess the influence of age on the treatment effect. During the six-month experimental period, Experimental Group 1 met three times a week while Experimental Group 2 had five weekly training sessions. All participants were subjected to the extended ALPHA battery of tests both at baseline and at the end of the study.ResultsThe Experimental Group 1 and Experimental Group 2 results showed a statistically significant difference (p = 0.005) between the initial and final measurements, suggesting that participation in a modern dance program had a positive impact on the transformation of morphological characteristics by increasing muscle mass and reducing subcutaneous fat. In addition, both experimental groups had a greater muscle strength, muscle endurance, and aerobic fitness at the end of the treatment.ConclusionThe study findings support the view that health-related physical fitness in young school-aged children can be improved through modern dance.